Strategi Marketing Mix Dalam Meningkatkan Volume Penjualan Menggunakan Analisis Swot Olahan Bawang Merah Pada PT. Sinergi Brebes Inovatif - Putri Ulfa; Syariefful Ikhwan; Dwi Harini (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to find out how to apply the marketing mix strategy and to find out the strengths, weaknesses, opportunities and threats in implementing the marketing mix strategy at PT. Innovative Brebes Synergy. Another goal is also to find out how the strategy at PT. Brebes Innovative Synergy in dealing with competitors with other companies that have the same product. This study used descriptive qualitative method. Data collection techniques using interview and documentation techniques. Data analysis using SWOT analysis. The place and its location at PT. The synergy of Innovative Brebes with the speakers, namely the General Manager and the Quality Control division. The results showed that the application of the marketing mix strategy at PT. The synergy of Innovative Brebes in the SWOT matrix is ​​in quadrant I. The strengths of the 4P marketing mix are: product, price, while the weaknesses are: promotion and price. The threat is promotion and place. The strategy in dealing with competitors with other companies that have the same product creates a strong brand image and maintains product quality to be able to differentiate the product from other products.